Holes in the wall: Examining gaps in knowledge in child and adolescent mental health in Tanzania – Scoping review. Issue 3 (5th January 2021) - Clarke, Ellisiv; Boshe, Judith; Spencer‐Rogers, Amelia; Jacques, Cara; Walker, Richard
Abstract: Objectives: To perform scoping review of the existing literature available specific to child and adolescent mental health in Tanzania. Methods: An extensive literature search of PubMed, Scopus, MEDLINE and EMBASE was undertaken to identify studies that focussed specifically on mental illness in children and young people in Tanzania. This included neurological and functional disorders, affective disorders, psychosis, epidemiological, intervention and treatment‐based studies. Qualitative analysis of the studies was then undertaken to assess what is currently known about the subject and how reliable this information is and to identify areas for further research. Results: Of 23 studies were included in the final synthesis, which could be broadly split into studies focussing on the prevalence and incidence of child and adolescent mental illness, hypothesised causes and correlations, identified treatments and interventions and qualitative studies of human experience. Conclusion: There is a dearth of published research regarding child and adolescent mental health in Tanzania. Although some high‐quality studies allow us good insight into the epidemiology of mental illness, interventional studies are often small and low‐power, and significant correlational relationships are yet to be drawn. There is significant scope for further child and adolescent mental health research in Tanzania. Abstract : Objectifs: Analyse de la portée de la littérature existante disponible spécifique à la santé mentale des enfants et des adolescents en Tanzanie. Méthodes: Une recherche documentaire approfondie de PubMed, Scopus, Medline et Embase a été entreprise pour identifier les études qui se concentraient spécifiquement sur la maladie mentale chez les enfants et les jeunes en Tanzanie. Cela comprenait des troubles neurologiques et fonctionnels, des troubles affectifs, des psychoses, des études épidémiologiques, d'intervention et basées sur le traitement. Une analyse qualitative des études a ensuite été entreprise pour évaluer ce que l'on sait actuellement sur le sujet, la fiabilité de ces informations et pour identifier des domaines pour des recherche plus approfondie. Résultats: 23 études ont été incluses dans la synthèse finale, qui pourrait être largement divisée en études axées sur la prévalence et l'incidence de la maladie mentale chez l'enfant et l'adolescent, les causes et corrélations hypothétiques, les traitements et interventions identifiés et les études qualitatives de l'expérience humaine. Conclusion: Il y a une pénurie de recherches publiées sur la santé mentale des enfants et des adolescents en Tanzanie. Bien que certaines études de haute qualité nous permettent de bien comprendre l'épidémiologie de la maladie mentale, les études interventionnelles sont souvent de petite taille et de faible puissance, et des relations de corrélation importantes doivent encore être établies. Il existe une marge de manœuvre importante pour plus de recherches sur la santé mentale des enfants et des adolescents en Tanzanie.